Bifunctionalized Metal–Organic Frameworks for Pore‐Size‐Dependent Enantioselective Sensing. Issue 25 (21st April 2022) - Han, Zongsu; Wang, Kunyu; Min, Hui; Xu, Jun; Shi, Wei; Cheng, Peng
Abstract: Porosity is a fundamental property of metal–organic frameworks (MOFs). However, the role of the pore size has always been underestimated in MOF‐based luminescent sensors for enantioselective sensing. The construction of isoreticular MOFs (IRMOFs) with variable pore sizes and the synergy between chirality and luminescence is challenging. Herein, a general strategy was developed to introduce chirality into two well‐known IRMOF‐74 analogs with nanochannels of identical shapes but different pore sizes by functionalizing the open metal site under mild conditions. To enhance the detection accuracy, a second luminescent center was introduced into the IRMOF‐74 system to achieve ratiometric sensing. The two bifunctionalized IRMOF‐74 compounds exhibited pore‐size‐dependent sensing performance for enantiomers. This study not only provides a convenient method to construct chiral MOFs as advanced sensing materials but also reveals the fundamental of the pores in MOF‐based luminescent sensors. Abstract : Porosity is fundamental in metal–organic frameworks (MOFs) but has always been underestimated for luminescent sensing applications. A simple and general synthetic strategy was developed for isoreticular MOFs with nanochannels of identical shapes but different pore sizes, which revealed the fundamentals of the pore effect in luminescent sensors.